Profile of the students' learning motivation of SDN Panunggangan 1 - Permatasari, Anisya Dinda; Fatihaturosyidah; Suratno, Tatang (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Learning motivation is an initiative that arises in students to do things to achieve success. The existence of motivation to learn, then provides encouragement and strength that causes students to want to act or behave. The motivation can be influenced by internal and external factors, both factors must balance to positively affect students in providing direction in achieving learning goals. If not, it will make the student not know the direction in achieving learning goals like at SDN Panunggangan 1. Based on the results of the questionnaire, there is an image obtained, where the learning motivation of SDN Panunggangan 1 students is in the medium category and it is known that the most dominant factors influencing students are family factors and internal factors. This is due to students who initially do not have motivation and their closest factors do not provide direction so that they are not encouraged in terms of learning, as a result there are students who are still behind in their thinking skills compared to other classmates. In fact, to be able to achieve the goal, you must have high motivation, which is driven by family, school, and the student itself. Their motivation is in the medium category. For this reason, this study uses a qualitative approach with a case study method and data collection is carried out using a questionnaire that is reinforced with the results of interviews and observations. The subjects of this study are grade 5 students who were selected by purposive sampling.
Keywords: learning motivation; intelligence; emotional; parenting